Employing Cooperative Learning to Enhance the University Students’ Reading Comprehension - Widiastuti, Ida Ayu Made Sri (LPPM Institut Pendidikan Nusantara Global, 2024)
Cooperative learning is considered one of the most effective learning methods to improve students’ language skills. Reading is an essential language skill for students in language learning. Therefore, this study was aimed at improving reading comprehension through cooperative learning. The result data showed that the score in each cycle improved significantly. The grand mean of the first cycle was 78.26, and 85.22 in the second. The grand mean score of the first and second cycles is much higher than the mean score of the initial reflection. Moreover, the questionnaire result showed comparative percentages of 41.62%, 41.62%, 16.76%, and 0% for items A, B, C, and D, respectively. The questionnaire results indicated that most of the students were actively engaged in learning reading comprehension. Therefore, this study implies that lecturers should utilize the cooperative learning method more intensively in teaching English.